MEMBANGUN CITRA MADRASAH MELALUI PROGRAM KELAS UNGGULAN DI MTSN 2 BANDAR LAMPUNG - Farida Hanun (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2016)
A preminent class is a class consisting of selectedstudents based on strict requirements which are academic potency, IQ and highly sufficient student creativity. MTsN 2 of Bandar Lampung has held the preminent class program. The research is aimed at finding out implementation of the Preeminent class program at MTsN 2 of Bandar Lampung by using the qualitative method. The research shows that: a) The implementation of the preeminent class program can improve Islamic schools’ image, b) Supporting factors of the implementation of the preminent class program are establishment of cooperation network between curriculum development team of MTsN 2 of Bandar Lampung and MGMP, availability of competent teachers, a proactive role of Islamic school committee in facilitating the implementation of the preeminent class program, c) Backstop factors are non-maximum students’ readiness in following the preminent class learning process, some of the students have not actively used English, lack of reward from the headmaster on performance of the students teaching the preeminent class, some of the teachers have not used multimedia facilities to their maximum extent, d) The Ministry of Religion shall notice the need of facilities and infrastructures for Islamic schools organizing preminent class program, and the need of teachers’ professionalism by holding workshops, seminars and work trainings.Kelas unggulan merupakan kelas yang berisi siswa pilihan yang diseleksi berdasarkan syaratsyarat yang ketat yaitu potensi akademik, IQ dan kreatitifitas siswa yang sangat memadai. MTsN 2 Bandar Lampung telah menyelenggarakan program kelas unggulan. Penelitian ini bertujuan untuk mengetahui pelaksanaan program kelas unggulan di mtsN 2 Bandar Lampung dengan menggunakan metode kualitatip. Hasil penelitian menunjukkan bahwa: a) penyelenggaraan program kelas unggulan dapat meningkatkan citra madrasah, b) faktor pendukung pelaksanaan program unggulan adalah terbentuknya jaringan kerjasama tim pengembang kurukulum MTSN 2 Bandar Lampung dengan mgmP, tersedianya guruguru yang berkompeten, peranan komite madrasah yang proaktif dalam memfasilitasi pelaksanaan program kelas unggulan, c) faktor penghambatnya adalah kesiapan siswa yang belum maksimal dalam mengikuti pembelajaran kelas unggulan, sebagian siswa belum aktif berbahasa Inggris, kurangnya reward dari kepala sekolah terhadap kinerja guru yang mengajar kelas unggulan, sebagian guru belum maksimal menggunakan sarana multimedia, d) Kementerian Agama perlu memperhatikan kebutuhan sarana prasarana pada madrasah yang menyelenggarakan program kelas unggulan, dan perlunya peningkatan profesionalisme guru melalui penyelenggraan workshop, seminar dan lokakarya.